2006
DOI: 10.1111/j.1420-9101.2006.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of B chromosomes and supernumerary segments on morphometric traits and adult fitness components in the grasshopper, Dichroplus elongatus (Acrididae)

Abstract: The South American species, Dichroplus elongatus, is polymorphic for B chromosomes and supernumerary segments in chromosome pairs M6 (SS6), S9 (SS9) and S10 (SS10). Both forms of supernumerary heterochromatin shape chiasma frequency and distribution and B chromosomes also affect male fertility. Here, we analysed the effects of these polymorphisms on morphometric traits (total, 3rd femur, 3rd tibia, thorax and tegmen lengths) and several adult fitness components, including male and female mating success, and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…There are differences among AMOVAs based on minisatellite loci and AMOVAs based on mtDNA sequences, showing male-biased gene flow. Additionally, different populations of D. elongatus have reproductive and morphological differences, including male sexual selection favouring larger individuals and phenotypic variation as a result of local adaptation to season length and number of generations along a latitudinal gradient [22], [84]. These selective differences may promote the dispersion of males to more favourable regions contributing to shape the observed scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are differences among AMOVAs based on minisatellite loci and AMOVAs based on mtDNA sequences, showing male-biased gene flow. Additionally, different populations of D. elongatus have reproductive and morphological differences, including male sexual selection favouring larger individuals and phenotypic variation as a result of local adaptation to season length and number of generations along a latitudinal gradient [22], [84]. These selective differences may promote the dispersion of males to more favourable regions contributing to shape the observed scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Population cytogenetic studies demonstrated that the persistence of B chromosomes in natural populations from Argentina may be explained mainly in a selective scenario. The maintenance on supernumerary chromosomes is the result of trade-offs among opposite selective effects and interactions with their mitotic instability [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, no direct mating preferences depending on the number of Bs are detected (Martin et al 1996), and no differences in mating success with respect to B chromosomes has been found in other populations (Lopez-Leon et al 1995). However, male Dichroplus elongates grasshoppers carrying B chromosomes appear to have reduced mating success (Rosetti et al 2007). Finally, in the wasp Nasonia vitripennis a paternal sex-ratio B chromosome (PSR, that is transmitted through sperm and convert diploid females into haploid males by destroying the non-B paternal chromosome in fertilized eggs), PSR males are just as successful in obtaining matings under competition as standard males (Beukeboom 1994).…”
Section: Pre-copulatory Choice In Relation To Sgesmentioning
confidence: 95%
“…Body size-related traits have been the center of many evolutionary studies describing intraspecific variability because they are easily observable characters on which natural selection may act. Many studies in insects have shown that body-size characters are usually associated with several adult fitness components in natural populations ( Santos et al 1988 , 1992 ; Hasson et al 1993 ; Norry et al 1995 ; Remis et al 2000 ; Colombo et al 2001 ; Rosetti et al 2007 ). Effects of natural selection shaping morphometric variation could differ over males and females, thus creating sexual size dimorphism (SSD) patterns ( Slatkin 1984 , Fairbairn 1997 ).…”
mentioning
confidence: 99%